Dom?nance of mater?al compos?t?on on mechan?cal propert?es of normal and h?gh strength grade b?nary blended geopolymer concrete - Addepalli Mallinadh Kashyap; Tanimki Chandra Sekhar Rao; N.V.Ramana Rao (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The utilisation of pozzolanic materials as the replacement to conventional cement material have the potentiality to mitigate the pollution caused by the émission of carbon based green house gases which are a main source for global warming problem. For every production of 1 ton of cement it was approximated that the emission of carbon based green house gases are about 1 ton. Keeping this in view, a new material called Geopolymer which was first coined by Davidovits has gained a lot of interest by the researchers. In this study, different molarity variations of NaOH in the order of 4M, 6M, 8M, 10M, 12M and 14M and also the blending of mineral admixtures like Fly Ash and Ground Granulated Blast Furnace Slag with percentages (50%+50%) and the mechanical properties of normal M30 and high strength grade M70 binary blended Geopolymer concrete were studied after 28 days of ambient curing and were reported. The test results revealed that the effect of molar concentration of NaOH at 12 M is effective and the optimum replacement of mineral composition of source materials is (50%+50%) fly ash and ground granulated blast furnace slag.